The EFFECTIVENESS OF ONLINE OFFLINE LEARNING MEDIA (MO2) BASED ON SMARTPHONE - Dedek Arindawan; Lambang Subagiyo; Evie Palenewen (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the effectiveness of online-offline media (MO2) on improving students' cognitive learning outcomes. This study is a true experiment with a total sample of 60 students (30 students who use smartphones and 30 students who do not) at SMA Negeri 1 Samarinda class XI science in biology subjects. The design of this study used a posttest-only control design. The sampling technique is purposive sampling. Data were analyzed using an independent sample t-test and an N-Gain test. The results of the independent t-test analysis showed that there was a difference in the increase in cognitive learning outcomes in the application of MO2 with a significance value of 0.00 <0.05. The results of the N-gain test showed that MO2 was effective in improving cognitive learning outcomes with a score of 78% (high category). The results of this study indicate that MO2 media is effective in improving student learning outcomes.